Canadian Public Opinion on Cannabis: How Far Out of Step With It Is the Existing Law? - Hathaway, Andrew D.; Erickson, Patricia G.; Lucas, Philippe (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2007)
Public attitudes in Canada are clecwly in fauour of loosening restrictions on cutnabispossession. opinion polls conducted oorcr the past few yems show that most Canadiarssupport decriminaliTing slmple possession cmd use of mmijtnna. Recent polls, moreo,uer,saggest that more than half faonw fuII legaliTation. Support for legal access for heabhpw'poses is higher; onll one in six adubs opposes this reform. National drug swueysoffer few fwrher details beyond the demogral>hic profiles that relatc to certain uiews. Thispaper nkes a closer lnok at public opinion based on a random househokl survey of Torontoarluhs (N=1 ,081). This allows us to identify adlinonal characteristics associated withopinions about cmtnabis reform. Consistent with the findings from national drug surueys,the maiority opposes the cwtent prohibition. Respondents also recogniTed potentialhealth concems in addition to aclnowledglng health benefits of ca.nabis and a uu.iety ofproblens with the existlng ktw. Public attitudes u'e broadly 'hcnm reduction' orientedszggestlng euidence-based, public heahh initiatiq.les would. go:rp.er wide support as a uiableahernatiq.te to qiminal conuols.R6sum6Il ne fait auatn doute que les Cavhiens appuient le rel%oochement des restrictions concernantIa possesslon de cannabis. Les sondages d'opinion men6s au cotns des demiiresanndes rlotilent que In plupmt des Canadiens sont en fauern de la ddcriminalisation de lasimp/r possession et de h consommation de ma'ijunna. De plus, des sc.tndages rlcents indiquent que plus dc lnmoiti| des Cawdiens appuientlabgalisation delamartiurma.IJnnomhe encore plus g|and de Cuvdiens appuient l'accd.s llgal d la marijwma pour desraisons de santd. Seul wl adulte srr siI s'oppos e d ln r\forme des mestues liglslatites. ksenqu rcs ncltionales sw la consommation de drogues fownissent seulement Etel4ues ren'seignements de plw que les o[>inions de cernins groupes de personnes. Le pr€sent rapport\tudie plus d fond L'opinion du public d pctrtir d'm d.chmtillon aliatoire d'adultes deToronto (n = 1 081). Cekt permet de cerner des cu'act1ristiErcs suppliment{tires associ6esaux opinions concernu"Lt la rdforme des meswes liglslatives applicables au ccutnabis .Comme l'indiqtrcnt les rdsulnts des enqu tes nationales sru la consommation de drogwes ,la ptupnt des reponfumts s'opposent d l' interdiction actuelle . ils sont conscients des uou.bles de santd possibles, des bienfaits du cannabis pow lt santA et des probhmes causds parIes lois en uigtettr. Dans I'ensemble,le public priuild.gie la . r\duction des mefaits , . Celnlaisse croire qu'il rdserverait un accu.eil fauorable aux initiatiues de santd publique foncl1.essw l.'expdrience clinique qui consntuent une solution de rechange qiable atu meswes decontrlle des actiuitds cwminelles.